Neocollyris (Stenocollyris) renenovaki sp. nov. with comparison to four similar species occurring in Borneo (Coleoptera: Cicindelidae) - Dheurle, Charles; Moravec, Jiří (Zootaxa, 2025)
Neocollyris (Stenocollyris) renenovaki sp. nov. is described as new to science from Northern Borneo, province of Sabah, Malaysia. The new species is compared to type specimens of Neocollyris (Stenocollyris) levigata (W. Horn, 1894), N. (S.) constricticollis (W. Horn, 1909), N. (S.) sarawakensis sarawakensis (Thomson, 1857), and N. (S.) glabrogibbosa (W. Horn, 1929), which are introduced with differential diagnoses and illustrations. In addition, characters, variability, possible relationships and distribution of five other taxa are discussed, although they also significantly differ from N. (S.) renenovaki sp. nov. The authors came to the conclusion that N. (S.) levigata, N. (S.) constricticollis, N. (S.) oblita Naviaux, 1995, N. (S.) polita Dheurle, 2016, N. (S.) sarawakensis macrodera (Chaudoir, 1864), N. (S.) constricticolloides Dheurle, 2016 and N. (S.) werneri Naviaux, 1995 constitute a N. (S.) sarawakensis species-complex. Habitus and diagnostic characters of all the type and other examined specimens are illustrated in colour photographs. A relief map of Borneo with records of the five revised species is presented.